National Outcomes of Venoarterial Extracorporeal Life Support in Patients with Chronic Kidney Disease - Oh Jin Kwon; Esteban Aguayo; Kevin Tabibian; Jeffrey Balian; Arjun Chaturvedi; Dariush Yalzadeh; Joseph Hadaya; Yas Sanaiha; Peyman Benharash (Surgery Open Science)
Background: Despite the increasing use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) as advanced circulatory support for acute cardiac and circulatory failure, its high morbidity and mortality have necessitated the identification of risk factors. The prevalence of chronic kidney disease (CKD) in VA-ECMO patients remains unclear, and its relationship with outcomes is not well established. Methods: A retrospective analysis was conducted on patients (≥18 years) undergoing VA-ECMO using the 2019–2021 Nationwide Readmissions Database. Patients were stratified into non-CKD, CKD 1–2, and CKD 3–5 based on renal disease severity. Those with end-stage renal disease requiring dialysis or prior renal transplant were excluded. The primary outcome was in-hospital mortality, while perioperative complications were secondarily assessed. Multivariable regression models were employed to assess the associations between CKD severity and outcomes across VA-ECMO indications. Results: Of an estimated 15,432 included for analysis, 11.7 % had CKD, with 84.7 % categorized as CKD 3–5. Following risk adjustment, CKD 3–5 was independently associated with increased odds of in-hospital mortality (AOR 1.32, 95%CI 1.10–1.59) and overall complications (AOR 1.72, 95%CI 1.09–2.72) compared to non-CKD. Additionally, both CKD 1–2 and CKD 3–5 were linked to increased risks of cardiac and acute renal failure complications. When assessed across VA-ECMO indications, CKD 3–5 was associated with the highest risk-adjusted mortality when used for postcardiotomy shock, cardiogenic shock, and mixed cardiopulmonary support. Conclusions: Advanced CKD is independently associated with increased mortality and perioperative complications in VA-ECMO patients, highlighting the association between preexisting renal dysfunction and adverse outcomes.